Research Progress of Spironolactone as an Antagonist of NRG1-ERBB4 Pathway in the Treatment of Cognitive Impairment in Schizophrenia. Issue 6 (6th January 2020) - Zhang, Hongwei; Dai, Zunxiao; Lin, Huali; Tian, Ruiping; Zhu, Jing
No abstract available